2020
DOI: 10.1016/j.ijfatigue.2020.105539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phase angle on crack growth mechanisms under thermo-mechanical fatigue loading

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Test TC026 shows the highest, TC010 the lowest crack growth rates under the same IP TMF test conditions [25] (see Figure 13). It is clear from Figure 11 that the number of tertiary ' is significantly higher than the number of secondary ' for the investigated microstructures.…”
Section: General Model Application To An-isothermal Tmf Testsmentioning
confidence: 86%
See 3 more Smart Citations
“…Test TC026 shows the highest, TC010 the lowest crack growth rates under the same IP TMF test conditions [25] (see Figure 13). It is clear from Figure 11 that the number of tertiary ' is significantly higher than the number of secondary ' for the investigated microstructures.…”
Section: General Model Application To An-isothermal Tmf Testsmentioning
confidence: 86%
“…The current state of the model is just able to capture the lower boundary region of the conducted IP tests. Microstructural evaluation conducted by John et al [25] showed a relationship between decreasing secondary ' size distribution and increasing crack growth rate under IP-TMF loading for RR1000. In addition, Li et al [27] showed the influence of the microstructure, especially tertiary ' for isothermal crack growth tests with different hold times.…”
Section: General Model Application To An-isothermal Tmf Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the high stress state at the crack tip with high ΔK level can promote the occurrence of creep damage as seen in RR1000, the creep damage may not have time to fully develop if the crack tip advances quickly enough at a high ΔK level as seen in Udimet 720Li. Ni-based superalloys [119][120][121], which is supported by the higher FCG rates associated with intergranular fractography under the in-phase (IP) loading conditions compared with out-of-phase (OP) testing associated with transgranular fractography, due to the increased temperature at peak stress and therefore increased time-dependent FCG. A few reviews of the interaction between environmental damage and fatigue in Ni-based superalloys can be found in [4,21,109].…”
Section: Creep-fatigue Crack Growthmentioning
confidence: 99%